Epidemiological Analysis of Cancer Patients Diagnosed With Cranial Metastasis at Initial Presentation - Ercan Kaya (Medsci Publications, 2024)
Introduction: Metastatic lesions are the most common brain tumors, comprising 52% of all cases. Early diagnosis is crucial to improve patient outcomes, but many cases remain undiagnosed until advanced stages. This study aimed to investigate the characteristics of patients diagnosed with brain metastasis concurrently with their primary malignancy, examine prognostic factors, and compare these findings with brain metastases of known primary origins. Method: A retrospective analysis was conducted on 184 patients between 18-80 years diagnosed with brain tumors between January 2018 and January 2019. Patient data were collected from clinical records, and statistical analyses were performed using SPSS 26.0. Results: Out of the total patients, 43% were diagnosed brain metastases. Among these, 33% had no known primary malignancy at diagnosis. In this group, 92.3% were over 50 years old, and 77% were male. The most frequent primary cancer was lung cancer (81%). Males had an average time to metastasis diagnosis approximately twice as long as females. A higher incidence of metastasis correlated with a lower Karnofsky Performance Score, indicating reduced operability and quality of life. Conclusion: Early diagnosis is critical to improving outcomes. Routine cranial imaging for patients over 50 may aid in early intervention.